Evaluation Of The Efficacy Of Iot Deployment On Petro-Retail Operations - et. al., Santanu Purohit, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
After the Internet revolution, Internet of Things (IoT) is expected to be the next big technological change, connecting equipment as well as everyday objects to help businesses explore new ways of creating and delivering value. In the Oil & Gas industry context, IoT has been deployed extensively in the upstream sector and also to some extent in the mid-stream sector. However, it’s implementation in the downstream (retail) sector has been limited. This paper explores the applicability and impact of deploying an IoT solution at a fuel retail outlet. In our experiment, a live outlet was chosen in Kolkata, where a limited IoT solution was deployed, for a period of 3 months. Our research shows that IoT implementation can yield significant operational benefits by reducing the response times, leading to increased operational uptime and hence sales. It can also help improve the root cause analysis process by providing increased data to identify the issue(s).